Bioethanol production from brewers' solid wastes by co-immobilized co-culture Aspergillus awamori-Saccharomyces cerevisiae - Tsaousi, Konstantina; Nikolaou, Sofia; Koutinas, Athanasios A.; Drouza, Chryssoula (My University, 2011)
The signing of the Kyoto Protocol (KP) in 1997 commands the substitution of fossil fuels by alternative fuels for the reduction of the emission of greenhouse gases. The Environmental strategy (EC, 1997) necessitated the increase of energy production from renewables. Utilization of Brewers’ Spent Grain (BSG) for starch hydrolysis and bioethanol production was studied. BSG is a solid agro-industrial waste material produced from the brewing process. Member countries of the European Community generate millions of tons annually, but their utilization still remains limited. Aspergillus awamori was used for starch conversion and Saccharomyces cerevisiae for sugar conversion to bioethanol. HPLC and GC-FID analysis were performed for the determination of produced sugars and bioethanol, respectively. Pretreatments of BSG were examined for the enhancement of hydrolysis rate and bioethanol concentration. Finally, a co-immobilized co-culture A. awamori–S. cerevisiae was used for bioethanol production. This system reduces the required time and the equipment cost. Both microorganisms were immobilized on delignified BSG. Electron microscope spectroscopy was used for the observation of cells immobilization. High conversion rate of BSG starch to bioethanol was achieved by this biological, low-cost and environmentally friendly method that could be applied in the utilization of starchy agro-industrial wastes.
Keywords: Bioethanol; Solid wastes; Fossil fuels; Biochemistry; Molecular Biology; Biotechnology; Applied Microbiology